TiO2 nanoparticles synthesized on graphene nanosheets with varied crystallinity for photocatalytic degradation of MB dye - Jain R.; Upadhyaya M.; Singh A.; Jaiswal R.P. (My University, 2025)
The incorporation of graphene into titania enhances photocatalytic activity, although the role of graphene remains debated. This study reconciles conflicting explanations in the literature and elucidates the improved photocatalytic behavior of titania nanoparticles supported on graphene sheets with varied crystallinity for the degradation of Methylene Blue (MB) dye. Specifically, crystalline graphene (ExG) and near-amorphous graphene (rGO, Ex-rGO), derived through physical and chemical methods, respectively, were employed as templates during the synthesis of titania (TiO2) nanoparticles. The rGO and Ex-rGO exhibited fewer graphene layers (∼3) than ExG (∼47 layers). The resulting TiO2/Ex-rGO and TiO2/rGO nanocomposites demonstrated significantly higher MB dye degradation (92.1 % and 79.2 %) than the unmodified TiO2 (60.5 %) and TiO2/ExG (70.7 %) after 2 hours of UV exposure. This study identified alterations in the mesoporous network of titania upon the incorporation of graphene, characterized by widely open pores in TiO2/rGO and TiO2/Ex-rGO with large average pore diameters of 12.99 nm and 13.78 nm, respectively, compared to the nearly blocked pores with a narrow diameter of 7.89 nm in reference TiO2. The enhanced photocatalytic activity in graphene-templated titania was attributed to rapid intra-porous molecular diffusion, a previously unreported factor. Additionally, nearly-amorphous rGO was identified as a superior template over ExG due to crystalline/amorphous heterojunctions in TiO2/rGO and TiO2/Ex-rGO, leading to reduced electron-hole recombination. Finally, a proposed computational approach estimated ‘accessible’ porosity, and Knudsen diffusion coefficients for the synthesized photocatalysts (reference-TiO2: TiO2/ExG: TiO2/rGO: TiO2/Ex-rGO as 1.05: 1: 1.48: 1.72), justifying the observed trends in MB dye degradation. © 2024 Elsevier Ltd